Salmonella Paratyphi Infection: Use of Nanopore Sequencing as a Vivid Alternative for the Identification of Invading Bacteria - Chmel, Martin; Bartoš, Oldřich; Beran, Ondřej; Pajer, Petr; Dresler, Jiří; Čurdová, Martina; Holub, Michal (Prague medical report, 2021)
In our study we present an overview of the use of Oxford Nanopore Technologies (ONT) sequencing technology on the background of Enteric fever. Unlike traditional methods (e.g., qPCR, serological tests), the nanopore sequencing technology enables virtually real-time data generation and highly accurate pathogen identification and characterization. Blood cultures were obtained from a 48-year-old female patient suffering from a high fever, headache and diarrhea. Nevertheless, both the initial serological tests and stool culture appeared to be negative. Therefore, the bacterial isolate from blood culture was used for nanopore sequencing (ONT). This technique in combination with subsequent bioinformatic analyses allowed for prompt identification of the disease-causative agent as Salmonella enterica subsp. enterica serovar Paratyphi A. The National Reference Laboratory for Salmonella (NIPH) independently reported this isolate also as serovar Paratyphi A on the basis of results of biochemical and agglutination tests. Therefore, our results are in concordance with certified standards. Furthermore, the data enabled us to assess some basic questions concerning the comparative genomics, i.e., to describe whether the isolated strain differs from the formerly published ones or not. Quite surprisingly, these results indicate that we have detected a novel and so far, unknown variety of this bacteria.
Keywords: Nanopore sequencing; Salmonella; lidé středního věku; Pathogen identification; břišní tyfus; Nanopore Sequencing; Typhoid Fever; Paratyphoid fever; nanopórové sekvenování; ženské pohlaví; lidé; Enteric fever; Middle Aged; Humans; Female; Salmonella paratyphi A